Heat and Mass Transfer Analysis of Chemically Reactive Powell-Eyring Nanofluid Flow Over a Wedge: A Numerical Approach - Agarwal, Pooja; Jain, Reema; Loganathan, K.; Udhayakumar, R. (Contemporary Mathematics, 2024)
The present study describes the effects of different parameters on heat and mass transfer phenomena in fluid flow across a wedge. A non-Newtonian chemically reactive Powell-Eyring nanofluid model is considered for analysis. The governing equations for the boundary layer regime are derived by applying the principles of mass, momentum, and energy conservation. Using similarity transformation, the partial differential equations (PDEs), with boundary conditions are converted into ordinary differential equations (ODEs). With prescribed boundary conditions in the free stream and at the wall, these equations are simplified into an ordinary differential equations system. This simplification is attained using appropriate scaling of similarity transformations which produce a number of important dimensionless control parameters. The computational solution to the nonlinear coupled boundary value problem is obtained using the bvp4c numerical tool in MATLAB. The effects of the various physical parameters on the energy, velocity and mass profiles are investigated through graphs and tables. Also, Nusselt number, skin friction coefficient, and Sherwood number are explored. Validation with previous studies is included.